The Durbin-Watson statistic to estimate the instantaneous variance of non-stationary stochastic processes with ARMA structure for noise process - Sánchez, Egar; Vinante, Carlos (Rev. Téc. Fac. Ing. Univ. Zulia)
Véase archivo PDF